Biodiversity, analysis of features of the helminth-faunistic complex of the Caucasian goats population and treatment of parasitic diseases - M. G. Abdurakhmanov (Юг России: экология, развитие)
On the territory of the Big Caucasus 60 kinds helminths are revealed at the Caucasian goats . The complex of actions on helminthiasis prevention is offered, including separate pasture of livestock , change of pastures, struggle against predators and application of salt briquettes with panacure.